PENGARUH DISIPLIN KERJA DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN PADA PT AGAF GLOBAL KREASINDO DI BEKASI TIMUR - Safiih, Abdul Rahman; Wahyuni, Anita Tri (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of discipline variables on employee performance, to determine the influence of morale variables on employee performance and to determine the influence of discipline and morale variables. simultaneous work on employee performance at PT Agaf Global Kreasindo Bekasi. The sample used was a saturated sampling technique, totaling 50 employees. Data collection techniques through primary and secondary data. Data analysis techniques use descriptive statistics, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient analysisdetermination, t test and f test. The research results show that: (1) Partially there is a influence between discipline on employee performance at PT. Agaf Global Kreasindo Bekasi, this can be proven from a simple linear regression equation Y = 9.801 + 0.658.(2) Partially there is a influence between work morale on employee performance at PT. Agaf Global Kreasindo Bekasi, this can be proven from the simple linear regression equation Y = 4.805 + 0.912. (3) Simultaneously there is a influence between discipline and work enthusiasm on employee performance at PT. Agaf Global Kreasindo Bekasi, this can be proven from the multiple linear regression equation Y = 5.760 + 0.489 f???????????????? 2.800 with a significance level of 0.000 <0.05.